Análise epistemológica da produção científica do grufopees (2013-2022): diálogos sobre pesquisa-ação na interface com a formação continuada na perspectiva da inclusão escolar - França, Barbara Rebecca Baumgartem (2023)
This study aims to analyze the scientific production of Grufopees/CNPq-Ufes between the years 2013 to 2022 on action-research in the interface with continuing education in the area of special education from the perspective of school inclusion, considering the historical-social and political-institutional contexts. It is based on quanti-qualitative research, of the bibliographical and documental type, based on the epistemological analysis of knowledge, in order to reveal the different theoretical-methodological levels and philosophical assumptions that cross the productions. For this, it takes the assumptions of the Theory of Communicative Action by Jürgen Habermas, seeking, through speech situations, speech acts and arguments put forward by the authors of scientific productions, to dialogue in search of consensus about the knowledge produced by the research group in the area of action-research and continuing education from the perspective of school inclusion. Thus, the research issue permeates the understanding of how action-research has been appropriated by Grufopees/CNPq-Ufes studies in the area of special education from the perspective of school inclusion which has as object the continuing education of education professionals. Throughout the process, the research has as participants the authorsresearchers of the selected productions, considering for the production, organization and categorization of the data two recording instruments: the “summary sheet”, by Messina (1999), for the mapping of the productions, and the “Epistemological Matrix” based on the studies of Régis Silva (2013) and Gamboa (2018), to carry out the epistemological analysis referring to the academic productions of eight master's dissertations. Data analysis is based on the method developed by studies by Almeida (2010), in order to dialogue with the internal aspects of the productions in the “Argumentative Circles”, based on the communicative rationality of the Habermasian philosophy, seeking to identify the relationships established between researcher and participants, the constitution of the research problem, the movements triggered in the research processes, as well as the understanding of the reality and the intentions of change. As a result, a strong performance of the group in transformation processes inherent to the theoretical-methodological perspective of collaborative-critical action research is evident, contributing to the development of structural changes, conceived collectively in the elaboration of processes of continued formation in the perspective of school inclusion and training policies in Espírito Santo municipalities. The perspective of action research defended by the group is part of a “tradition” of research groups that, through research and extension projects, have promoted collaboration with different contexts, in search of emancipation of the subjects involved and social transformation. As a whole, the investigative processes analyzed in this study present ethical potential when they think of new ways of conceiving the continuing education of education professionals through the collaborative-critical path, ensuring, through the production of knowledge with the other, critical self-reflection, listening sensitive and attentive, mobilizations resistant to the prevailing neoliberal order.